Urdu ka guldasta (khususi isha$1 (Bat): motia class 1s - Fozia, Ahsan Farooqui (Oxford University Press Karachi, 2022)
"Urdu ka Guldasata: Motia Class 1" is a comprehensive Urdu language textbook designed to introduce young learners to the foundational aspects of Urdu reading, writing, and comprehension. Through engaging activities and colorful illustrations, this book aims to foster a love for the Urdu language in young minds. The textbook covers a wide range of topics, including alphabets, words, sentences, and basic grammar rules.